Konstruk Sosial dan Teknologi: Fenomena Penggunaan Fitur Close Friend dalam Second Account Instagram - I Kadek Candika Wira Angga; Hafiz Bimo Nugroho (Jurnal Riset Komunikasi (JURKOM), 2025)
The phenomenon of using the close friend feature on second Instagram accounts reflects the growing need for more intimate interaction spaces in the social media era. This study aims to explore how social construction shapes user behavior in utilizing this feature. The research uses a qualitative descriptive method with the Social Construction of Technology (SCOT) as the theoretical framework. Data were collected through in-depth interviews with six purposively selected informants. Findings indicate that the use of the close friend feature on second accounts is not only a form of privacy control but also a social strategy to maintain exclusive emotional bonds. Users perceive this feature as a safe space for self-expression, free from public norms. In conclusion, Instagram’s second account and close friend feature represent a technological adaptation to the evolving social needs of its users.